Interrelationships of the Threskiornithidae and the phylogenetic position of the Miocene ibis 'Plegadis' paganus from the Saint‐Gérand‐le‐Puy area in central France. (18th June 2013) - De Pietri, Vanesa L.; Collinson, Martin
<x xml:space="preserve">Abstract</x> The fossil ibis Plegadis paganus is known from the Early Miocene of the Saint‐Gérand‐le‐Puy area, France. It was first described in the 19th century by Milne‐Edwards (1867–1868), who noticed similarities with members of the extant genera Eudocimus and Plegadis, a view endorsed by subsequent descriptions. The fossil's present placement within the genus Plegadis is not supported by synapomorphic features, and important differences with members of this genus have been noted in the past. The present analysis demonstrates that retention of P. paganus in the extant genus Plegadis is no longer justified, and it is therefore referred to the new genus Gerandibis. A phylogenetic analysis of 55 osteological characters supports placement of Gerandibis pagana in a clade together with Neotropical taxa. This analysis also allowed for an evaluation of the relationships among extant threskiornithids. Contrary to results obtained in molecular‐based phylogenies, the present analysis supports a basal divergence of crown group Threskiornithidae into a clade comprising Threskiornis and Platalea and a clade comprising all other ibises. Within the latter, two clades, one made up of Old World taxa and the other consisting predominantly of New World taxa, were recovered.